2011
DOI: 10.1016/j.devcel.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of Simultaneous GATA1/2, RUNX1, FLI1, and SCL Binding in Megakaryocytes Identifies Hematopoietic Regulators

Abstract: SummaryHematopoietic differentiation critically depends on combinations of transcriptional regulators controlling the development of individual lineages. Here, we report the genome-wide binding sites for the five key hematopoietic transcription factors—GATA1, GATA2, RUNX1, FLI1, and TAL1/SCL—in primary human megakaryocytes. Statistical analysis of the 17,263 regions bound by at least one factor demonstrated that simultaneous binding by all five factors was the most enriched pattern and often occurred near know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
262
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(284 citation statements)
references
References 69 publications
16
262
0
Order By: Relevance
“…We also observed strong enrichment of binding motifs for ETS family transcription factors, which are known to co-operate with GATA1 in megakaryocytic differentiation (60% and 52%). 4,43 We then mapped each peak location to the closest transcription start site and assigned the peaks to the categories: upstream (2-100kb), promoters (0-2kb), intragenic, downstream (0-100kb), and gene desert (>100kb). This analysis revealed that the GATA1 peaks were significantly enriched at promoters and intragenic regions and significantly depleted in gene desert regions compared to randomly distributed genomic regions, consistent with the expected locations for gene regulatory regions ( Figure 3E).…”
Section: Chip-seq Analysis Of Gata1 and Gata1s In G1me Cells Reveals mentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed strong enrichment of binding motifs for ETS family transcription factors, which are known to co-operate with GATA1 in megakaryocytic differentiation (60% and 52%). 4,43 We then mapped each peak location to the closest transcription start site and assigned the peaks to the categories: upstream (2-100kb), promoters (0-2kb), intragenic, downstream (0-100kb), and gene desert (>100kb). This analysis revealed that the GATA1 peaks were significantly enriched at promoters and intragenic regions and significantly depleted in gene desert regions compared to randomly distributed genomic regions, consistent with the expected locations for gene regulatory regions ( Figure 3E).…”
Section: Chip-seq Analysis Of Gata1 and Gata1s In G1me Cells Reveals mentioning
confidence: 99%
“…As a master transcriptional regulator, GATA1 directs global gene expression to specify terminal erythroid or megakaryocytic fate. [1][2][3][4][5] It accomplishes this by both activating lineage specifying genes and repressing progenitor maintenance genes through a variety of gene regulatory mechanisms that depend on context-dependent co-factor interactions. 6 Importantly, GATA1 interacts with and controls the expression of many other lineage-specifying transcription factors to co-ordinately repress factors promoting other cell fates while activating those of megakaryocytes and erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…After antibody incubation, 500 mL washing buffer PBE buffer (PBS [Sigma-Aldrich] at pH 7.2, 2 mM EDTA [Sigma-Aldrich], and 0.5% BSA [Sigma-Aldrich]), and 5 mg/mL 7-amino actinomycin D (7-AAD; Invitrogen) were added. Flow cytometric analysis of MKs and EBs was performed according to the method previously described (Macaulay et al 2007;Tijssen et al 2011) using the following antibodies: human anti-CD41a-APC clone HIP8, anti-CD42a-FITC clone ALMA.16, anti-CD235a-FITC clone GA-R2 (HIR2), and anti-CD34-PE clone 581 (BD Biosciences). All samples were analyzed on the CyAn ADP 9-Color flow cytometer using the software Summit v4.3.02 (Beckman Coulter).…”
Section: Cell Morphology and Flow Cytometric Analysismentioning
confidence: 99%
“…Supplemental Table 2 and Supplemental Table 3 give an overview of the peak data sets. ChIP-seq data sets in primary MKs were obtained from Tijssen et al (2011) (GEO accession no. GSE24674).…”
Section: Peak Calling and Binning Strategymentioning
confidence: 99%
“…The main transcription factors that regulate Mk differentiation and maturation are RUNX1, FLI1, GATA-1, GATA-2, NF-E2, and TAL1/SCL. These factors act synergistically, often bound in complexes, for the coordinated activation and repression of genes required for development of mature Mks [15]. Mk development is also regulated by a complex cross-talk between Mk and cells, cytokines, and extra-cellular matrix (ECM) proteins of the surrounding bone marrow (BM) microenvironments [13].…”
Section: Overview Of Platelet Biogenesismentioning
confidence: 99%